A sustainable approach to the development of highly degradable packaging films of pectin/guar gum/polyvinyl pyrrolidone: Thermal, biodegradation, and mechanical studies with statistical optimization. Issue 22 (3rd February 2022) - Lal, Sohan; Kumar, Vinod; Jagdeva, Geetanjali; Arora, Sanjiv; Kumar, Parvin; Gulati, Kapil; Singh, Omvir
Abstract: The use of synthetic packaging materials and mulch films has retrogressive environmental effects. To replace these synthetic materials, high strength biodegradable polymer blends are synthesized using pectin, guar gum and polyvinyl pyrrolidone (PVP). The ternary blends are prepared with guar gum (10%–50%) and PVP (30%–50%), using the solvent casting technique. The experimentation is carried out using a 5 × 3 factorial design and analyzed by response surface methodology. Analysis of variance test is applied to analyze the ultimate tensile strength (UTS) and elongation at break and their simultaneous optimization is done by the desirability index method. The maximum desirability index value (0.877) is achieved at a guar gum content of 50% and PVP content of 41.73%. At this composition, the estimated value of UTS is 24.57 MPa and elongation at break is 27.29%. The thermal stability of the blends is almost similar and they are stable up to 170°C. Initial biodegradation (upto 30 days) of blends increases by 54.82% for samples with higher PVP content and decreases by 43.60% with the increase in guar gum content. All the blends are degraded completely within 90 days. The high tensile properties, sustained thermal stability and complete biodegradation of blends enable these for applications like packaging and agriculture mulch films. Abstract : Pectin based biodegradable composites films are fabricated with guar gum and polyvinyl pyrrolidone (PVP) using solvent casting method. Addition of guar gum and PVP has improved the tensile strength of films and composition of components is optimized on the basis of tensile properties. Composites are thermally stable up to 175°C and also completely biodegradable.